Physical Activity Trajectories and Quality of Life in Older Adults - De Moraes-Ferrari, G (Wroclaw University of Health and Sport Sciences, 2023)
Purpose. Physical activity (PA) is associated with a better quality of life and well-being in older adults. Examining PA trajectories, especially increasing habitual PA habits, makes it possible to better understand how PA behavioural changes may impact health and quality of life. This study aimed to analyse the longitudinal association between 2-year PA trajectories (changes in intensity and frequency) and quality of life. Methods. Participants were 6.057 older adults aged 50 years (2,331 men) from 13 European countries. Regression models were performed to analyse the effects of PA trajectories on older adults’ quality of life. Results. Men and women who engaged in more PA had significantly higher quality of life scores than those with lower PA levels. At follow-up, those who increased PA frequency to more than once a week, at both moderate and vigorous intensity, had a greater quality of life score (men’s moderate PA: = 1.13, p < 0.001; men’s vigorous PA: = 1.93, p < 0.001; women’s moderate PA: = 1.77, p < 0.001; women’s vigorous PA: = 1.72, p < 0.001). Conclusions. Increasing the frequency of moderate and vigorous intensity PA is associated with a better quality of life in older adults. Even in later life, changes in lifestyle components, such as PA, can significantly increase the quality of life. Thus, public health should encourage promoting PA as an effective strategy to improve healthy ageing and hinder vulnerability in older ages. © Wroclaw University of Health and Sport Sciences.